2003
DOI: 10.3758/cabn.3.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate deficit in associative recognition relative to item recognition in global amnesia

Abstract: In two experiments, we tested the hypothesis that medial temporal lobe (MTL) amnesic patients and, likewise, diencephalic (DNC) amnesic patients evidence a disproportionate deficit in memory for associations in comparison with memory for single items. In Experiment 1, we equated item recognition in amnesic and control participants and found that, under these conditions, associative recognition remained impaired both for MTL patients and for DNC patients. To rule out an alternative interpretation of the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
91
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 27 publications
13
91
0
1
Order By: Relevance
“…Previous findings have provided evidence for the relational processing theory by showing that the MTL is necessary for conjunction memory over long delays (Cermak, 1976;Winocur and Weiskrantz, 1976;Chun and Phelps, 1999;Giovanello et al, 2003) (but see Stark and Squire, 2001). Our work extends the relational processing theory (Cohen and Eichenbaum, 1993;Eichenbaum, 1999) by showing that the MTL is necessary for relational processing at delays as short as 8 s.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous findings have provided evidence for the relational processing theory by showing that the MTL is necessary for conjunction memory over long delays (Cermak, 1976;Winocur and Weiskrantz, 1976;Chun and Phelps, 1999;Giovanello et al, 2003) (but see Stark and Squire, 2001). Our work extends the relational processing theory (Cohen and Eichenbaum, 1993;Eichenbaum, 1999) by showing that the MTL is necessary for relational processing at delays as short as 8 s.…”
Section: Discussionsupporting
confidence: 67%
“…MTL amnesics have profound difficulties in remembering learned word pairs as compared with single words (Cermak, 1976;Winocur and Weiskrantz, 1976;Giovanello et al, 2003;Turriziani et al, 2004). Several neuroimaging studies have reported greater activations in MTL structures during encoding (Henke et al, 1997;Davachi et al, 2003;Kirwan and Stark, 2004;Ranganath et al, 2004) and retrieval (Yonelinas et al, 2001;Giovanello et al, 2004) of the relationship between stimuli as opposed to separate stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas many studies report a disproportionate effect of hippocampal damage on recollection and associative memory relative to familiarity (Huppert and Piercy 1978;VarghaKhadem et al 1997;Holdstock et al 2002;Yonelinas et al 2002;Giovanello et al 2003;Mayes et al 2004;Aggleton et al 2005), other reports find that hippocampal damage impacts familiarity and recollection to a similar extent (Manns and Squire 1999;Stark et al 2002;Manns et al 2003;Cipolotti et al 2006;Wais et al 2006;Jeneson et al 2010;Kirwan et al 2010;Song et al 2011). Interestingly, a patient with significant perirhinal damage that spared the hippocampus showed impaired familiarity and preserved recollection (Bowles et al 2007).…”
Section: Hippocampus and Mtlmentioning
confidence: 99%
“…These studies provide striking evidence for selective involvement of the perirhinal cortex in familiarity but not recollection, and for the hippocampus and parahippocampal region in recollection, not familiarity. Several studies have reported that transient hypoxia, which more significantly affects the hippocampus than parahippocampal region, results in disproportional deficits in memory for associations or context compared to item recognition (Mayes et al, 2002;Giovanello et al, 2003;Turriziani et al, 2004;Holdstock et al, 2005). One study that used a receiver operating characteristic (ROC) analysis showed that mildly hypoxic patients exhibited severe deficits in recollection, but normal familiarity (Yonelinas et al, 2002).…”
Section: Hippocampusmentioning
confidence: 99%